DISTRIBUTION AND GEOINFORMATION DATA OF ISKANDARIA KUSCHAKEWITSCHI (HERZENSTEIN, 1890) IN WATER BASINS OF FERGANA VALLEY (Scientific journal of the Fergana State University, 2026)
The occurrence of Iskandaria kuschakewitschi is reported from several water bodies in the Fergana Valley, and a geographical map of its distribution range has been developed. New occurrence points were identified in multiple locations along the Kara Darya River, as well as in several small streams and rivers, including Tentaksoy and Shahrikhonsoy (Andijan region); Chortoqsoy and Chodaksoy (Namangan region); Oltiariqsoy, Margilonsoy, and Isfayramsoy (Fergana region), along with the Great Fergana Canal and some collector waters. Based on these findings, extensive geoinformation data for the species was compiled for the first time during this study. Taxonomic-geographical considerations regarding the distribution of I. kuschakewitschi are discussed, and the hypothesis that the populations from the Chirchik, Dukentsoy, and Ohangaron rivers may taxonomically constitute a different species is substantiated.